Factors Influencing Community Interest in Savings at Bank XYZ Branch: Analysis Comparative Model - Lestari, Sandi; Fakhri, Ulumuddin Nurul; Nuriyah, Aminah; Sunandar, Nandar (Tazkia Islamic Finance and Business Review, 2023)
The imbalance between the number of Indonesian Muslims and the interest in saving in Islamic banks makes for a very interesting problem to study. This study aims to look at the factors that influence interest in saving in sharia banks, especially the Bank XYZ Branch. This research uses descriptive and quantitative methods. The tools used are distributing questionnaires to 43 Bank XYZ Branch customers with the likerts approach; besides that, this research uses two models, namely the ANN (artificial neural network) and partial least squares (PLS-SEM) models. The sample obtained from this study was 43 customers with various professions. The result of this research is that the religious knowledge factor is the factor that most influences interest in saving, with a value of 42.02%, followed by a promotional factor of 38.36%. While the product factor is not very influential with a value of only 19.61%, it is no different from the results of PLS-SEM, namely that religious knowledge and promotion are the most influential things significantly, while bank products do not affect saving in Islamic banks. The results of this study can help Islamic banking parties, especially the Bank XYZ Branch, map prospective customers who want to be prospected.